2017
DOI: 10.1038/s41559-016-0061
|View full text |Cite
|
Sign up to set email alerts
|

Diminishing-returns epistasis decreases adaptability along an evolutionary trajectory

Abstract: Populations evolving in constant environments exhibit declining adaptability. Understanding the basis of this pattern could reveal underlying processes determining the repeatability of evolutionary outcomes. In principle, declining adaptability can be due to a decrease in the effect size of beneficial mutations, a decrease in the rate at which they occur, or some combination of both. By evolving Escherichia coli populations started from different steps along a single evolutionary trajectory, we show that decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
93
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(107 citation statements)
references
References 29 publications
9
93
5
Order By: Relevance
“…With epistasis, mutation sub-stitutions that are deleterious in one genetic context may even be necessary in another context for a population to reach the global peak. This dependence predicts a rugged landscape, although an experimental test did not support this prediction (Wünsche et al 2017). In almost all alternative environments, however, the relevant intermediate steps become beneficial.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…With epistasis, mutation sub-stitutions that are deleterious in one genetic context may even be necessary in another context for a population to reach the global peak. This dependence predicts a rugged landscape, although an experimental test did not support this prediction (Wünsche et al 2017). In almost all alternative environments, however, the relevant intermediate steps become beneficial.…”
Section: Discussionmentioning
confidence: 97%
“…Theoretical models predict that later substituting mutations will often depend on earlier mutations for their benefit (Draghi and Plotkin 2013;Blanquart et al 2014). This dependence predicts a rugged landscape, although an experimental test did not support this prediction (Wünsche et al 2017). By contrast, when mutations that are selected together in one environment are then tested in another, they seem more likely to act independently.…”
mentioning
confidence: 94%
“…As a consequence of these mutations, specific pathways of TRN, which are irrelevant to the present selection pressure, are inactivated (48). However, the fitness benefit of these TF mutations decline over time, likely as a consequence of diminishing returns epistasis (49), and as adaptation decelerates, selective constraints play a bigger role in the mutation frequency. In a well adapted population, the optimal variants of TFs are maintained by purifying selection.…”
Section: Discussionmentioning
confidence: 99%
“…Applying the results of this experiment to natural phytoplankton population requires taking into account how population size and diversity (among other factors, such as recombination rates) affect adaptation (53). Previous work has shown that higher standing genetic variation can allow adapting populations to evolve faster (54)(55)(56)(57). Similarly, recombination and plasticity (1, 58) can both speed up adaptation (59).…”
Section: Discussionmentioning
confidence: 99%